Status of Breeding Water Birds in Changthang Cold Desert Sanctuary, Ladakh - Hussain, Syed Ainul; Pandav, Bivash (Indian Forester, 2008)
The status of water birds in and around 11 lakes and 10 marshes in the Changthang Cold Desert Sanctuary, Ladakh was examined during July - August 2001. During the survey 44 species of water birds were recorded of which 19 species were breeding in various wetlands. Thirteen species were recorded at Stratsapuk Tso, seven from Tso Kar and six species each from Tso Moriri, Tsigul Tso, Lam Tso and Ya Ya Tso. Among the marshes, Puga valley and Phukche had more breeding species than other wetlands. Evidence of Greylag Goose Anser anser breeding in Ladakh was recorded from Lam Tso, Chumur. Large congregations of Ruddy Shelduck Tadorna ferruginea were recorded in Tso Kar, Stratsapuk Tso and Tso Moriri and of Bar-headed Geese Anser indicus and Great Crested Grebe Podiceps cristatus at Stratsapuk Tso. During the study 42 Black-necked Cranes were recorded from 15 sites of which nine pairs had juveniles with them. Maximum number of cranes was recorded from the Hanle plains, Fukche and Chusul marshes. In spite of such biodiversity value the wetlands in the Changthang are under increasing pressure and need an integrated management approach for effective conservation.